An ethnobotanical study on medicinal plants used for equine digestive health in Kazakhstan - Talgat Ibragimov; Saltanat Arystanova; Roza Abildaeva; Altynay Senkebaeva; Kamila Muminova; Khalima Kidirbayeva; Yerzhan Issayev; Aydarkhan Balabekov (Caspian Journal of Environmental Sciences)
Kazakhstan's rich cultural heritage includes traditional knowledge of plant-based remedies for animal health. This study aimed to document the ethnobotanical knowledge of medicinal plants used to treat equine digestive disorders in Kazakhstan, focusing on identifying culturally significant plants, their modes of preparation, and administration. Ethnobotanical data were collected through semi-structured interviews and participatory observation with 70 informants, including horse breeders, traditional healers, and community elders across three regions of Kazakhstan. Plant specimens were collected, identified, and deposited in a national herbarium. Data were analyzed using descriptive statistics and ethnobotanical indices, including Use Value (UV), Informant Consensus Factor (ICF), and Fidelity Level (FL). The survey documented 40 plant species from 24 families used in treating equine digestive disorders. Glycyrrhiza uralensis (UV = 0.86), Ferula assa-foetida (UV = 0.79), and Artemisia absinthium (UV = 0.74) were among the most frequently cited plants. Roots and aerial parts were commonly used, often prepared as decoctions (37.5%) or infusions (30.0%). High informant consensus was observed for treatments of gastric ulcers (ICF = 0.939) and diarrhea (ICF = 0.929). Artemisia absinthium showed the highest fidelity (FL = 98.08%) for treating intestinal parasites. The majority of informants (54.3%) reported acquiring their ethnobotanical knowledge through family traditions, and 82.9% practiced selective harvesting for conservation. This study reveals the rich ethnobotanical knowledge of the Kazakh community regarding equine digestive health. The high consensus among informants suggests a well-established traditional knowledge system.